1996
DOI: 10.1093/ajcp/106.5.680
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Disorders Associated With Deletions of Chromosome 20q:A Clinicopathologic Study of 107 Patients

Abstract: H e m a t o l o g i c D i s o r d e r s A s s o c i a t e d W i t h D e l e t i o n s o f C h r o m o s o m e 2 0 qA Clinicopathologic Study of 107 Patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 22 publications
1
47
0
4
Order By: Relevance
“…111 It is a common finding, for example, not only in PV, [53][54][55] but also in PMF [26][27][28]112 and may occur in ET, 114,115 chronic neutrophilic leukaemia, 62 myelodysplastic syndromes 113,114 and acute myeloid leukaemia, 115 although rarely in lymphoproliferative malignancies. 116,117 It is mostly found as an isolated event, although in approximately a quarter of cases it can occur with additional cytogenetic abnormalities including deletion 5q, monosomy 7, trisomy 8, deletions and translocations of 13q and trisomy 21. 117 The 20q breakpoints appear to be heterogeneous, as evidenced by the variable size of the deletion by standard cytogenetics, 118 FISH analysis 119 and by the early molecular studies, which demonstrated the variable retention of the SRC gene.…”
Section: Chromosome 20mentioning
confidence: 99%
See 1 more Smart Citation
“…111 It is a common finding, for example, not only in PV, [53][54][55] but also in PMF [26][27][28]112 and may occur in ET, 114,115 chronic neutrophilic leukaemia, 62 myelodysplastic syndromes 113,114 and acute myeloid leukaemia, 115 although rarely in lymphoproliferative malignancies. 116,117 It is mostly found as an isolated event, although in approximately a quarter of cases it can occur with additional cytogenetic abnormalities including deletion 5q, monosomy 7, trisomy 8, deletions and translocations of 13q and trisomy 21. 117 The 20q breakpoints appear to be heterogeneous, as evidenced by the variable size of the deletion by standard cytogenetics, 118 FISH analysis 119 and by the early molecular studies, which demonstrated the variable retention of the SRC gene.…”
Section: Chromosome 20mentioning
confidence: 99%
“…116,117 It is mostly found as an isolated event, although in approximately a quarter of cases it can occur with additional cytogenetic abnormalities including deletion 5q, monosomy 7, trisomy 8, deletions and translocations of 13q and trisomy 21. 117 The 20q breakpoints appear to be heterogeneous, as evidenced by the variable size of the deletion by standard cytogenetics, 118 FISH analysis 119 and by the early molecular studies, which demonstrated the variable retention of the SRC gene. 120,121 Such a conclusion was confirmed by Nacheva et al, 113 who showed variable size deletion using highresolution banding, with a commonly deleted region spanning 20q11.2-q13.1.…”
Section: Chromosome 20mentioning
confidence: 99%
“…Deletion of the long arm of chromosome 20 is a common cytogenetic ®nding in myeloproliferative diseases (MPDs), especially in polycythemia vera (p. vera) patients, where it is often the sole change (Mertens et al, 1991;Aatola et al, 1992;Dewald and Wright, 1995;Mitelman, 1995;Kurtin et al, 1996). The 20q deletion is also identi®ed cytogenetically in approximately 5% of myelodyplastic syndrome (MDS) patients, and in a fraction of acute myeloid leukemia (AML) cases, generally in association with other abnormalities (Kurtin et al, 1996, Mitelman, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of the long arm of chromosome 20 is a common cytogenetic ®nding in myeloproliferative diseases (MPDs), especially in polycythemia vera (p. vera) patients, where it is often the sole change (Mertens et al, 1991;Aatola et al, 1992;Dewald and Wright, 1995;Mitelman, 1995;Kurtin et al, 1996). The 20q deletion is also identi®ed cytogenetically in approximately 5% of myelodyplastic syndrome (MDS) patients, and in a fraction of acute myeloid leukemia (AML) cases, generally in association with other abnormalities (Kurtin et al, 1996, Mitelman, 1995. Deletion of 20q has been rarely observed in lymphoproliferative disorders (Mitelman, 1995) and in lymphoblastoid cell lines derived from MDS or Ph-positive acute lymphoblastic leukemia patients (Hollings et al, 1995) indicating that the deletion may have occurred in a progenitor cell with both myeloid and lymphoid potentiality Hollings et al, 1994;Knuutila et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…20q abnormalities are found in hematological disorders including the myeloproliferative disorders, especially polycythemia vera where it is identified in ϳ10% of the patients (4), the myelodysplastic syndromes, and in a fraction of acute myeloid leukemias cases (5)(6)(7)(8).…”
mentioning
confidence: 99%